Membaca Pemikiran Arkoun Tentang Etika Politik Islam - Rahawarin, Yunus (Jurnal Ushuluddin: Media Dialog Pemikiran Islam, 2017)
Lack of concern towards ethics in politics is a major problem occurring in political practice. This, indeed, opposes the noble mission of politics as an art of state management. Hence, it needs a commitment to deal with political ethics as a behavior synergic with political acts. Moreover, it is necessary to consider that political ethics should ideally become political identity. Based on this, this article will discuss political ethics in contemporary Islam based on Mohammed Arkoun’s perspective. Through content analysis of his works, this article will explore Arkoun’s criticism toward established concept of "Madinah State" particularly in its relation to political ethics. According to Arkoun, epistemology in Islam should be considered as historical product which is merely applicable in a particular time. Product of thought may not be relevant in all conditions and space; therefore, it cannot be implemented without time constrains. Most of Muslim intellectuals firmly believe that Madinah State is an ideal model of Islamic state. In Arkoun’s viewpoint, this belief may only be applicable during the Caliphate periods, approximately between 622 AD. and 1258 AD. He emphasizes that there are no Qur’anic or Hadith texts enforcing Muslims to obey the system of Madinah State. The most important one, in his opinion, is political ethics due to its very essential and universal entity. What has happened along the history of a state may be applied to improve and influence its established political system. In this context, political ethics is not merely about whether a state is either Islamic or secular, but it is about a state that consistently implements ethics in its political system.